PENGARUH METODE DISCOVERY LEARNING DENGAN MEDIA POWTOON TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Nesta Olivia; Firman; Desyandri (STKIP Subang, 2022)
This study aims to determine the effect of the discovery learning method assisted by poowtoon media on the mathematics learning outcomes of fifth grade students at SD Negeri 06 Kampung Lapai. This type of research is experimental research. The population of this study were all students of class V Negeri 06 Kampung Lapai for the 2022/2023 school year with a total of 30 students. Samples were taken by means of random sampling, obtained by students of class V-B as the experimental class and students of class V-A as the control class. Data collection techniques using tests. The results showed that the average score of learning outcomes after being given treatment in the experimental class was 99.2 and 97.7 in the control class. Hypothesis testing shows tcount > ttable, where tcount is 0.317 > ttable 0.206 then H0 is rejected and H1 is accepted. It can be interpreted that the discovery learning method assisted by powtoon media has an effect on the learning outcomes of mathematics in fifth grade students at SD Negeri 06 Kampung Lapai.